Topical Application of Arnica and Mucopolysaccharide Polysulfate Attenuates Periorbital Edema and Ecchymosis in Open Rhinoplasty: A Randomized Controlled Clinical Study. Issue 3 (March 2016) - Simsek, Gokce; Sari, Elif; Kilic, Rahmi; Bayar Muluk, Nuray
Abstract : Background: The purpose of this study was to investigate the effects of local arnica and mucopolysaccharide polysulfate treatment on the regression of postoperative edema and ecchymosis in patients who have undergone open technique rhinoplasty. Method: One hundred eight patients were included in the study. Participants were randomized into three groups, all of whom had undergone rhinoplasty. Group 1 ( n = 36) received postoperative arnica cream treatment, and group 2 ( n = 36) received postoperative mucopolysaccharide polysulfate cream treatment. Group 3 ( n = 36, control group) consisted of patients who received no postoperative local treatments. Patients were evaluated for 24 hours on days 2, 5, 7, and 10 after the operation. For the evaluation of postoperative edema and ecchymosis, a scale ranging from 0 to 4 was used, and the groups were compared. Results: In groups 1 and 2, postoperative ecchymosis was significantly less than in the control group during postoperative days 1, 5, and 7 ( p < 0.005). The regression of the edema was also more rapid in groups 1 and 2 than in the control group during evaluations on postoperative days 1, 5, and 7 ( p < 0.005). Neither edema nor ecchymosis was significantly different between groups 1 and 2 ( p > 0.005). Conclusions: The authors' results suggest that a rapid regression of edema and ecchymosis may be achieved by local treatments of arnica and mucopolysaccharide polysulfate cream. In addition, there are no significant differences between these two treatment regimens. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.